VD_FINDINFO HC / 2012 / 80 vom 23. Januar 2012 - VD Tribunal cantonal (2012)
OBLIGATION D'ENTRETIEN, PROTECTION DE L'UNION CONJUGALE, PROTECTION DE LA PERSONNALITÉ | 176 al. 1 CC, 28 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)